Urgensi Pendidikan Multikultural di Sekolah Dasar Sebagai Upaya Pencegahan Konflik Sosial Sejak Dini - Mochammad Miftachul Huda; Bunyamin Maftuh; Nanda William (Elementary Teacher Education Program, Majalengka University, 2023)
Indonesia is a pluralistic country that is faced with a challenge in social life. One of the social problems that often occurs in Indonesia is the conflict between individuals or groups on behalf of community organizations, ethnic groups, and cultures, one of which is caused by intolerance. Thus, an educational approach is needed that aims to prevent conflict early on. Multicultural education is an educational approach that is oriented towards developing the human potential to develop an attitude of respect for various kinds of diversity. This study is a literature review that aims to produce an analytical description of multicultural education in terms of concept, internalization of multicultural education in elementary schools, and the role of multicultural education in early conflict prevention efforts in elementary schools. Data collection was done by searching for articles according to the topic using the Publish or Perish application. The results of this study are that the concept of multicultural education is the process of teaching an attitude of acceptance of diversity; multicultural education in schools can be done by integration in all types of subjects; multicultural education plays a role in early conflict prevention efforts that can be realized in appreciating differences and diversity of learner backgrounds, social status, beliefs, and ethnicity, culture.